Optimization of a synbiotic formulation of soy yoghurt containing yacon extract by response surface methodology - Pauly-Silveira, Nadiége Dourado [UNESP]; Bedani, Raquel [UNESP]; Cavallini, Daniela Cardoso Umbelino [UNESP]; Manzoni, Maria Simone Jovenasso [UNESP]; Miguel, Daniela Peres [UNESP]; Borsato, Dionisio; Rossi, Elizeu Antonio [UNESP] (My University, 2010)
A synbiotic yoghurt based on a combination of soymilk and yacon water extract (from yacon root tubers) was developed as a novel food product fermented with a probiotic culture of Enterococcus faecium CRL 183 and Lactobacillus helveticus ssp jugurti 4l6. Response surface methodology (RSM) was used to optimize the independent variables soymilk protein concentration and percentage of yacon extract in the formulation through a Central Composite Rotatable Design (CCRD), consisting of a 22 factorial design with two levels (-1, +1), two central points (0) and four axial points (± a, 0) (0, ± α). The responses were assessed by consumer acceptance tests. The optimization indicated that a formulation with a soymilk protein concentration of 1.74g/L and 25.86% of yacon extract gave the best average values, 5.91 for the taste and 6.00 for the overall impression responses. The formulation with 40% of yacon extract and the same concentration of soymilk protein achieved similar acceptance values: taste (5.94) and overall impression (5.87), however, with the extra yacon, it probably had a greater content of prebiotic fructooligosaccharides. Consequently, both formulations may give useful functional foods, with sensory properties comparable with those of soy yoghurt (control formulation). Copyright © 2010 by New Century Health Publishers.
Keywords: Prebiotics; Probiotics; Response surface methodology; Soy yoghurt; Yacon; plant extract; probiotic agent; protein; Smallanthus sonchifolius extract; soy yoghurt; soymilk protein; synbiotic agent; unclassified drug; yoghurt; concentration (parameters); Enterococcus faecium; factorial design; fermentation; independent variable; Lactobacillus helveticus; nonhuman; response surface method; Smallanthus sonchifolius; soybean milk